Analisis Daya Terima Konsumen Terhadap Wortel Sebagai Substitusi Pandan Dalam Pembuatan Klepon - Wijaya, Michelle; Rosanto, Stephanie (CV RIFAINSTITUT, 2023)
Carrots are vegetables that tend to taste sweet, even though many people don't like to eat carrots because of the unpleasant aroma of carrots. Carrots contain good nutrition and have many benefits for the human body. Researchers use klepon as a medium to innovate with carrots because klepon has a low nutritional content. Researchers used 3 methods, namely carrot water, water and carrot pulp, and carrot puree with a ratio of 60%, 80% and 100% respectively. In this experiment the researchers used organoleptic tests, hedonic tests, F tests and nutritional tests. The results obtained are the average obtained that product 2 is the product that has the greatest level of preference, respondents stated